Penetapan Simultan Kadar Fenilpropanolamin Hidroklorida dan Klorfeniramin Maleat dalam Tablet secara Spektrofotometri - FARIDAH FARIDAH; NOVI YANTIH; NETTY HERAWATI (Fakultas Farmasi Universitas Pancasila, 2008)
Simultaneous determination of phenylpropanolamine hydrochloride and chlorpheniramine maleate in tablets by spectrophotometry was carried out. The method is based upon total absorption of the two compounds in a mixture which can be applied to quantify each ofthe component. The absorption of phenylpropanolamine hydrochloride and chlorpheniramine maleate in 0.1 N hydrochloric acid were measured at the maximum Wavelength of phenylpropanolamine hydrochloride (256.7 nm) and that of chlorpheniramine maleate (262.6 nm), with a correlation coefficient of 0.999. A high precision could be obtained as shown by the CV of 0.2139-0.4962% for phenylpropanolamine hydrochloride and 0.3182- 0.5289% for chlorpheniramine maleate, While the recoveries ofphenylpropanolamine hydrochloride and chlorpheniramine maleate were 99.93% ± 0.43% and 99.76% ± 0.39%, respectively. The proposed method is simple, with a high accuracy and suitable for the simultaneous determination ofphenylpropanolamine hydrochloride and chlorpheniramine maleate in tablets, Without prior separation.